MAPPING LEACHATE CONTAMINATION USING RESISTIVITY GEOELECTRIC METHOD AT TPA KEBON KONGOK, WEST LOMBOK REGENCY, WEST NUSA TENGGARA PROVINCE - Ramadhan, Muhammad Hisyam Ramadhan; Budihardjo, Mochamad Arief; Kasiyati, Kasiyati (Indonesian Physical Review, 2025)
TPA Kebon Kongok is one of the Final Processing Sites in Indonesia that uses a sanitary landfill system. The limited availability of land and the increasing height of the waste pile that has been dumped during the TPA operation period and the discovery of leachate puddles at several points in the TPA area are problems that need to be addressed immediately so as not to disturb the environmental ecosystem and society. The purpose of this research is to determine the depth of leachate pollution in the subsurface and map the leachate distribution pattern around the TPA Kebon Kongok area. This research was conducted using the resistivity geoelectric method with a 2-D Wenner configuration in 10 lines and the Self Potential (SP) method with an area 132,732 mÂ² and 138 data point. Based on data analysis, it is found that the layer indicated as leachate has a resistivity value of 0.143-4.71 Î©m. Based on the results of the SP analysis, it is known that the accumulated leachate streams are interpreted to have relatively lower self-potential values with anomalous values of -100 mV to -40 mV. Low potential values were found in the northwest to southeast of the study site, while relatively high potential values were found in the southern part of the study site. The direction of leachate distribution in various directions is due to the fact that the study area has different elevations and the subsurface layer is composed of layers that easily drain liquids, which are indicated as sand layers. This research is expected to be a consideration for the management of TPA Kebon Kongok in taking mitigation steps from leachate pollution.